CARBON EMISSION AND ABSORPTION OF AMELIORANT AMENDMENTS IN PEAT SOIL PADDY RICE - SUSILAWATI, H.L.; SETYANTO, P.; ARIANI, M. (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2011)
Agricultural land extensification on peat land is one solution to fulfill national needed on food. Peat soil contains organic matter therefore it becomes one source of greenhouse gas emissions (GHG), i.e. Dioxide carbon (CO2), metahne (CH4), and NO2. Land use for agricultural activities will change the natural condition of peat soil. The changes could increase GHG emissions. One way to reduce GHG emissions and to increase rice production in peat soils is by adding of ameliorant. The aim of this study was to determine the effect of ameliorant on carbon balance at peat soil paddy rice. The experiment was conducted at research station of Agricultural Environmental Research Institute in 2008. Samples of peat soil as much as 8 tons was carried from South Kalimantan and placed into 12 microplots. The size of microplot was 1.5 x 1.5 x 0.8 m. Experimental design used randomized block design with four treatments: control, dolomite 2 t ha-1, rice straw 2 t ha-1 and animal manure 2 t ha-1 which was repeated three times. Rice variety was Batanghari and transplanted at age 21 days after seeding. Fluxes of CH4 were measured automatically using GC which equipped with FID (Flame Ionization Detector). Emissions of CO2 and N2O were measured manually using GC which equipped with ECD detector (electron capture detector) and TCD (thermal conductivity detector). The content of organic carbon in plants was determined by dichromate oxidation technique-titration. The lowest of net carbon/ carbon budget is animal manure treatment: 4,962.0 kg-C ha-1 followed by dolomite, without ameliorant, and rice straw: 5,270.2; 9,534.7; and 10,115.6 kg-C/ha respectively. The highest yield is rice straw, followed by dolomite, without ameliorant and manure: 4.98, 4.92, 4.69, and 4.54 t ha-1 respectively. Dolomite treatment has the highest ratio of yield GWP-1 : 933.58 kg of yield/ton of CO2-C followed by animal manure 913.30 kg of yield /ton of CO2-C, without ameliorant and rice straw: 492.13 and 491.59 kg of yield/ton of CO2-C respectively.